THE EFFECTIVENESS OF USING TIME TOKEN AREND STRATEGY TO IMPROVE STUDENT’S SPEAKING ABILITY - Defitta Ardiman Putri; Siska fahlevi; Dian Mega Putri (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2022)
Abstract This study aims to determine the effect of using the Time Token Arend strategy on the ability to speak English in class VIII MTsN 1 Mentawai Islands. This research is a quantitative research that uses a pre-experimental method, with a one group pre-test-posttest design. In the experimental class, treatment is given using the Time Token Arend strategy. The population of this study is class VIII MTsN 1 Mentawai Islands academic year 2021/2022, totaling 78 people consisting of 3 classes namely VIII 1, VIII 2 and VIII 3. The sample class is determined by homogeneity and normality tests, which are selected as experimental classes is VIII 2. The instrument used is a speaking test. The results of the students' English speaking ability scores were analyzed using the pre-test and post-test patterns. After averaging, the average pretest score is 60.56 and the posttest average is 74.08. After the t-test, it is known that the t-count value is greater than the t-tables value (9.14> 2.06). Testing this hypothesis is done by t-table test, after doing t-count = 9.14 is greater than t-tables = 2.06 in the level of significance of 0.05. Thus, the findings state that the hypothesis in this study is accepted, because using the time token arend strategy has an effect on students' English speaking skills. Keywords: Effectiveness, Time Token Arend, Speaking Ability AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh penggunaan strategi Time Token Arend terhadap kemampuan berbahasa Inggris siswa kelas VIII MTsN 1 Kepulauan Mentawai. Penelitian ini merupakan penelitian kuantitatif yang menggunakan metode pra eksperimen, dengan rancangan one group pre-test-posttest design. Pada kelas eksperimen diberikan perlakuan dengan menggunakan strategi Time Token Arend. Populasi penelitian ini adalah siswa kelas VIII MTsN 1 Kepulauan Mentawai tahun ajaran 2021/2022 yang berjumlah 78 orang yang terdiri dari 3 kelas yaitu VIII 1, VIII 2 dan VIII 3. Kelas sampel ditentukan dengan uji homogenitas dan normalitas, yang dipilih sebagai kelas eksperimen adalah VIII 2. Instrumen yang digunakan adalah tes berbicara. Hasil skor kemampuan berbicara bahasa Inggris siswa dianalisis dengan menggunakan pola pre-test dan post-test. Setelah dirata-ratakan, rata-rata nilai pretest adalah 60,56 dan rata-rata posttest adalah 74,08. Setelah dilakukan uji t diketahui bahwa nilai t hitung lebih besar dari nilai t tabel (9,14 > 2,06). Pengujian hipotesis ini dilakukan dengan uji t-tabel, setelah dilakukan t-hitung = 9,14 lebih besar dari t-tabel = 2,06 pada taraf signifikansi 0,05. Dengan demikian, temuan tersebut menyatakan bahwa hipotesis dalam penelitian ini diterima, karena penggunaan strategi time token arend berpengaruh terhadap kemampuan berbicara bahasa Inggris siswa.Kata kunci: Efektivitas, Time Token Arend, Kemampuan Berbicara